FORMATION OF TECHNICAL PREPARATION OF SCHOOLCHILDREN IN THE PROCESS OF PHYSICAL EDUCATION - Abdilkhakim Turdievich Jumayev (European Science Publishing, 2024)
The article describes the experience of obtaining and applying the targets of technical preparedness of schoolchildren. The application of the method of questioning and calculation of the concordance coefficient made it possible to single out the indicators of the technique of eight test motor exercises that determine the physical preparedness of schoolchildren.
Keywords: school physical education lesson, learning process, the schoolchildren, indicators of exercise techniques, technical preparedness.